KIDNEY HISTOPATHOLOGICAL FEATURES OF WHITE RATS (RATTUS NORVEGICUS) ADMINISTERED MORINGA (MORINGA OLEIFERA) LEAF SIMPLICIA AFTER LEAD EXPOSURE - Winda Audia Ananda; I Ketut Berata; Ida Bagus Oka Winaya; Ni Luh Eka Setiasih; Samsuri Samsuri; Ni Nyoman Werdi Susari (Buletin Veteriner Udayana, 2026)
Lead (Pb) exposure can induce nephrotoxicity through oxidative stress and inflammation, resulting in histopathological alterations in the kidneys. Moringa (Moringa oleifera) leaves contain antioxidant and anti-inflammatory compounds with potential nephroprotective effects. This study aimed to describe renal histopathological lesions in lead-exposed white rats and evaluate the effects of Moringa leaf simplicia administration following lead exposure. Twenty male Wistar rats were divided into four groups (n=5): P0, placebo; P1, Pb acetate 0.5 mg/rat/day for 3 days; P2, Pb acetate for 3 days followed by Moringa leaf simplicia 0.1 g/rat/day for 14 days; and P3, Pb acetate followed by Moringa leaf simplicia 0.6 g/rat/day for 14 days. On day 15 after administration of the test substance, the kidneys were collected and processed into histopathological slides stained with hematoxylin and eosin. Congestion, inflammation, and necrosis were assessed in five fields of view using a 0–3 scoring system for each. Significant differences were observed among the groups for all parameters. At 0.6 g/rat/day, the degree of congestion and inflammation decreased compared to the Pb-only group, whereas the 0.1 g/rat/day dose showed no difference. Necrotic lesions were still observed in all Pb-exposed groups and did not differ significantly among the groups receiving simplicia. It was concluded that Moringa leaf simplicia at 0.6 g/rat/day can improve congestion and inflammation following Pb exposure but has not yet improved necrotic lesions. Further studies with longer durations and higher doses are required.